Evaluation of tenogenic differentiation potential of selected subpopulations of human adipose‐derived stem cells - Gonçalves, A I (2019)
Identification of a suitable cell source and bioactive agents guiding cell differentiationtowards tenogenic phenotype represents a prerequisite for advancement of cellâ based therapies for tendon repair. Human adiposeâ derived stem cells (hASCs) are apromising, yet intrinsically heterogenous population with diversified differentiationcapacities. In this work, we investigated antigenicallyâ defined subsets of hASCsexpressing markers related to tendon phenotype or associated with pluripotency thatmight be more prone to tenogenic differentiation, when compared to unsortedhASCs. Subpopulations positive for tenomodulin (TNMD+ hASCs) and stage specificearly antigen 4 (SSEAâ 4+ hASCs), as well as unsorted ASCs were cultured up to 21days in basic medium or media supplemented with TGFâ Î²3 (10 ng/ml), or GDFâ 5(50 ng/ml). Cell response was evaluated by analysis of expression of tendonâ relatedmarkers at gene level and protein level by real time RTâ PCR, western blot, and immu-nocytochemistry. A significant upregulation of scleraxis was observed for both sub-populations and unsorted hASCs in the presence of TGFâ Î²3. More prominentalterations in gene expression profile in response to TGFâ Î²3 were observed forTNMD+ hASCs. Subpopulations evidenced an increased collagen III and TNC deposi-tion in basal medium conditions in comparison with unsorted hASCs. In the particularcase of TNMD+ hASCs, GDFâ 5 seems to influence more the deposition of TNC.Within hASCs populations, discrete subsets could be distinguished offering variedsensitivity to specific biochemical stimulation leading to differential expression oftenogenic components suggesting that cell subsets may have distinctive roles in thecomplex biological responses leading to tenogenic commitment to be further exploredin cell based strategies for tendon tissues.